Real Time Integrated Navigation System (INS) for Land vehicles using H-Infinity filter - Pooja Ahuja S, Divakar Harekal, Veena GS (International Journal of Advanced Science and Technology, 2020)
The idea and results of Integration of a strapdown inertial Navigation system (INS) MEMS inertial sensors and the NEMA global positioning system (GPS) for the motivations of land vehicle navigation have been introduced in this paper. This system is built for the Navigation guidance for the User in absence of the GPS Signals. The integration is made by a usage of H-Infinity conspire, both for the underlying arrangement and Navigation stages. Conventional coordination design (centralized and cascaded) are essentially Built on the utilization of high-precision inertial sensors. The thought behind this paper is Development of an Algorithm is done utilizing low-precision inertial sensors (MPU6050) and GPS as the fundamental wellspring of a navigation data, while the adequate exactness of INS is accomplished by the suitable damping of INS blunders. The predetermined benefits of damping coefficients can have diverse impact contingent upon the reality whether the moving item is moving or is moving with a constant speed during the interims of absence of GPS information. The investigation of incorporated navigation system performance is made tentatively utilizing the information gained along the genuine land vehicle’s trajectory and by Artificial introduction of interims of absence of GPS information on the parts described both by move and by constant velocity, and by fluctuating the estimations of blunder damping coefficients. Keywords—GPS, H-Infinity filter, INS, Navigation, Global Positioning System